(untitled) (El Hilo de la Fabula, 2021)
In drama studies, the theoretical category ’documentary theatre’ (Weiss,[1968] 2017; Vezzero, 2017; Pavis, 1998) is one of the least studied contemporary dramatic forms. Usually, the study of document drama is included within the more general notion of ’political theater’ (Piscator, 1976) Brecht,[1948] 1983; Badiou, 2011, 2015; Pavis, 1998; Irazabal, 2004). All theater can be considered political, however, the theoretical notion formulated by Erwin Piscator dates back to the first decades of the XX century. Piscator used Marxist theory to analyse theater and collected his ideas and experiences in his book Political Theatre, published in 1929, where the author devotes an entire chapter to documentary plays, which he links unfailingly to the philosophy of historical materialism. Documentary theatre can be considered a demarcation or a derivation of this notion, as it is created on the borderline between fiction and reality and works especially with the ideas of archive and document or primary source. It is also in Germany where this creative experience is formalized, especially from Peter Weiss’s theater and theoretical ideas (1968). Documentary theatre confronts the classic definition of dramatic theatre, often confused with the denomination of docudrama, historical drama, or biodrama, documentary theater pretends not to be fictional and to be starred by those actually involved in the real event being staged. That is to say, the documentary value lies in the appropriation of a real story, the semiotic activation of theatrical inputs (texts, photos, screenings, costumes, objects, testimonies) that come from that real event and, in addition, the fact that it is played by the people involved in that event. In Argentina, the writer, theatre and film director and performer Lola Arias is the one who feels and recognizes herself as part of the lineage of the 20th century’s German theatre and, especially, of Weiss’ theatre. This article will analyze the presence of documentary theatre in her work, but, especially, in Campo minado (2016- 2020), a play that brings together three Argentine veterans and three British marines on stage to narrate and document the Malvinas War’s experience and traumatic effects